2013
DOI: 10.3354/meps10283
|View full text |Cite
|
Sign up to set email alerts
|

Field test of the behavioral regulation of larval transport

Abstract: The maintenance of marine populations depends on the completion of larval migrations between adult and larval habitats, but the ability of microscopic larvae to regulate their movements in such a dynamic environment has been debated. Using a comparative hypothesis testing approach and intensive hourly sampling throughout the water column, we determined the ability of larvae of 6 species with different swimming abilities (2 gastropods, 2 crabs, 2 fishes) to overcome strong tidal mixing during spring tides and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 67 publications
0
25
0
Order By: Relevance
“…The absence of lowsalinity water is typical in low-inflow estuaries from late spring to fall along the West Coast, and the effects of turbulence and the lack of a low-salinity cue on larval depth regulation should be examined. If turbulent mixing is important in disrupting vertical migrations, then (1) weakly swimming ciliated larvae, such as mollusks and echinoderms, should be even less able to regulate depth effectively while stronger swimming fish larvae should be better able to do so (Kunze et al 2013) and (2) larvae should be better able to regulate depth in deeper well-mixed estuaries. If freshwater inflow and lower salinity is important, then tidal vertical migrations should occur in estuaries with substantial freshwater inflow, but not in low-flow estuaries when larvae are abundant, regardless of estuary depth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The absence of lowsalinity water is typical in low-inflow estuaries from late spring to fall along the West Coast, and the effects of turbulence and the lack of a low-salinity cue on larval depth regulation should be examined. If turbulent mixing is important in disrupting vertical migrations, then (1) weakly swimming ciliated larvae, such as mollusks and echinoderms, should be even less able to regulate depth effectively while stronger swimming fish larvae should be better able to do so (Kunze et al 2013) and (2) larvae should be better able to regulate depth in deeper well-mixed estuaries. If freshwater inflow and lower salinity is important, then tidal vertical migrations should occur in estuaries with substantial freshwater inflow, but not in low-flow estuaries when larvae are abundant, regardless of estuary depth.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we determined the effectiveness of larval behavior by benthic crustaceans in regulating larval transport between a low-inflow estuary and coastal waters. We hypothesize that previously documented larval behaviors in adjacent coastal waters may not be evident in the estuary due to tidal vertical mixing and turbulence in shallow water (Breckenridge and Bollens 2011;Kunze et al 2013) or the lack of low salinity or pronounced salinity fluctuations to cue tidal vertical migrations (Miller and Morgan 2013a). Thus, we concurrently looked for vertical migrations in adjacent nearshore waters where salinity fluctuations are similar, but tidal flows and the strength of vertical mixing are weaker.…”
Section: Communicated By Judith P Grasslementioning
confidence: 99%
See 1 more Smart Citation
“…Numerous field studies have identified vertical shifts in larval distribution that coincide with tidal (Carriker 1951(Carriker , 1961Kunkle 1957;Wood and Hargis 1971;Booth 1972;Maru et al 1973;Andrews 1983;Gregg 2002;Baker and Mann 2003;Knights et al 2006;Kunze et al 2013;Peteiro and Shanks 2015) and diel (Quayle 1952;Maru et al 1973;Tremblay and Sinclair 1990a;Raby et al 1994; cycles. Such distribution shifts occur in taxa with both strongly (e.g., crustaceans ;Queiroga 1998;Forward and Tankersley 2001) and weakly (e.g., mollusks, echinoderms, bryozoans, and sponges; Young and Chia 1987;Kingsford et al 2002) swimming larvae, as well as in holoplankton (Southward and Barrett 1983;Harding et al 1986;Scrope-Howe and Jones 1986).…”
mentioning
confidence: 99%
“…Reef fish larvae, for example, orientate towards odours and sounds of their natal reef and use directional currents to get there (Paris and Cowen 2004;Leis et al 2011;Paris et al 2013). Observations of larvae moving along hydraulic gradients (Stoll and Beeck 2012), adapting swimming and drifting speeds to the prevailing flow regime (Hogan and Mora 2005) or regulating depth distribution according to currents (Kunze et al 2013), further emphasize an active response to the hydrodynamic environment. The interactive effects of temporally unstable hydrodynamics and ontogenetically variable larval behaviour are increasingly being used in oceanic dispersal models to gain more realistic simulation results (Vikebo et al 2011;Sponaugle et al 2012;Nolasco et al 2013).…”
Section: Introductionmentioning
confidence: 99%